Phylogenetic Patterns of Swainsonine Presence in Morning Glories - Quach, Quynh N.; Gardner, Dale R.; Clay, Keith; Cook, Daniel (Frontiers in Microbiology, 2022)
Endosymbionts play important roles in the life cycles of many macro-organisms. The indolizidine alkaloid swainsonine is produced by heritable fungi occurring in diverse plant families including locoweeds (Fabaceae) and morning glories (Convolvulaceae) plus two species of Malvaceae. Swainsonine is known for its toxic effects on livestock following the ingestion of locoweeds and potential for pharmaceutical applications. We sampled and tested herbarium seed samples (n=983) from 244 morning glory species for swainsonine presence and built a phylogeny based on available ITS sequences of the sampled species. We show that swainsonine occurs only in a single morning glory clade and host species are established on multiple continents. Our results further indicate that this symbiosis developed ~5 mya and that swainsonine-positive species have larger seeds than their uninfected conspecifics.